MAKNA GARIS MIRING (/) PADA FRASA “UU/PERPPU” - Septiyani, Samriananda (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2021)
AbstractArticle 22 paragraph (1) Constitution of the Republic of Indonesia Year 1945 gives the President attributive authority to determine PERPPU in compelling emergencies. The position of PERPPU is regulated in Article 7 paragraph (1) letter c of Law No. 12 of 2011 with the formulation of the phrase